Review of Indo-West Pacific jawfishes (Opistognathus: Opistognathidae), with descriptions of 18 new species - Smith-Vaniz, William F. (Zootaxa, 2023)
Sixty species of jawfishes (Opistognathus) from the Indo-West Pacific are reported in an updated review, including descriptions of 18 new species: Opistognathus albomaculatus n.sp., O. asper n.sp., O. aurolineatus n.sp., O. bathyphilus n.sp., O. biporus n.sp., O. challenger n.sp., O. erdmanni n.sp., O. flavidus n.sp., O. helvolus n.sp., O. hyalinus n.sp., O. megalops n.sp., O. microspilus n.sp., O. nigripinnis n.sp., O. parvus n.sp., O. pholeter n.sp., O. triops n.sp., O. vigilax n.sp., and O. wassi n.sp.. Species accounts are provided for each species, including illustrations or color photographs, complete synonymies, specimens examined (or appropriate citation if previously published in detail), diagnosis, comparisons, etymology, and distribution maps. Geographic range extensions are reported for a number of species. An identification key is given for all species and frequency tables of important characters are also provided. The taxonomic status of Opistognathus inornatus and O. rosenbergii annulatus are discussed in detail but not completely resolved pending unavailable molecular data. Geographic variation is also described for Opistognathus adelus, O. albomaculatus n.sp., O. castelnaui, O. margaretae, O. variabilis, and O. vigilax n.sp. Many species are known only from holotypes and others from single localities, indicating how much more remains to be known about these jawfishes.